Optimization of Cost and Time in Fulfilling Furniture Raw Materials Through the Utilization of Kepelan Wood Waste: A Case Study at CV Dijawa Abadi, Jepara - Ahmad Mubais; Siti Nur Halisa; Dholiful Hadi (Pro-ELLitera, 2025)
This study aims to identify the impact of using kepelan wood waste to optimize production costs and time at CV Dijawa Abadi. Furniture industry waste at CV Dijawa Abadi has become an increasing problem due to accumulating waste in storage areas. This situation occurs due to the lack of waste utilization and delays in waste collection by buyers at CV Dijawa Abadi. This study analyzes wood waste at CV Dijawa Abadi by identifying waste according to wood thickness. The research adopts a qualitative descriptive approach, collecting data through four months of observation, interviews, and documentation. The data is analyzed and compared with materials from vendors. The results indicate that utilizing kepelan wood waste can minimize furniture production costs and time. These findings serve as a reference for furniture entrepreneurs to be more creative in running their businesses by optimizing material utilization for high-quality products. Keywords: Optimization, Kepelan Wood Waste, Cost and Time, Production